Enhanced Stretchable and Sensitive Strain Sensor via Controlled Strain Distribution - Chen, Huamin; Lv, Longfeng; Zhang, Jiushuang; Zhang, Shaochun; Xu, Pengjun; Li, Chuanchuan; Zhang, Zhicheng; Li, Yuliang; Xu, Yun; Wang, Jun (Nanomaterials (Basel, Switzerland), 2020)
Stretchable and wearable opto-electronics have attracted worldwide attention due to their broad prospects in health monitoring and epidermal applications. Resistive strain sensors, as one of the most typical and important device, have been the subject of great improvements in sensitivity and stretchability. Nevertheless, it is hard to take both sensitivity and stretchability into consideration for practical applications. Herein, we demonstrated a simple strategy to construct a highly sensitive and stretchable graphene-based strain sensor. According to the strain distribution in the simulation result, highly sensitive planar graphene and highly stretchable crumpled graphene (CG) were rationally connected to effectively modulate the sensitivity and stretchability of the device. For the stretching mode, the device showed a gauge factor (GF) of 20.1 with 105% tensile strain. The sensitivity of the device was relatively high in this large working range, and the device could endure a maximum tensile strain of 135% with a GF of 337.8. In addition, in the bending mode, the device could work in outward and inward modes. This work introduced a novel and simple method with which to effectively monitor sensitivity and stretchability at the same time. More importantly, the method could be applied to other material categories to further improve the performance.